The situationality of human-animal relations : perspectives from anthropology and philosophy - Breyer, Thiemo; Widlok, Thomas (Human-animal studies (Series : Bielefeld, Germany), 2018)
Riding, hunting, fishing, bullfighting: Human-animal relations are diverse. The anthology presents various case studies of situations in which humans and animals come into contact and asks for the anthropological and philosophical implications of such encounters. The contributions by renowned scholars such as Garry Marvin, Albert Piette, and Kazuyoshi Sugawara present multidisciplinary methodological reflections on concepts such as embodiment, emplacement, or the "conditio animalia" (in addition to the "conditio humana") as well as a consideration of the term "situationality" within the field of anthropology